2022
DOI: 10.1038/s41598-022-14935-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early innate and adaptive immune responses to the TB vaccine Mycobacterium bovis BCG and vaccine candidate BCGΔBCG1419c

Abstract: The vaccine Mycobacterium bovis Bacillus Calmette-Guérin (BCG) elicits an immune response that is protective against certain forms of tuberculosis (TB); however, because BCG efficacy is limited it is important to identify alternative TB vaccine candidates. Recently, the BCG deletion mutant and vaccine candidate BCGΔBCG1419c was demonstrated to survive longer in intravenously infected BALB/c mice due to enhanced biofilm formation, and better protected both BALB/c and C57BL/6 mice against TB-induced lung patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Steigler et al showed that intranasal vaccination of mice resulted in increased levels of ILC1, ILC2, and ILC3 within lungs, 4 weeks post-immunization [ 41 ]. This is supported in future studies by Gunasena et al, showing increased levels of ILC1 and ILC3 in the tissue samples from lungs, liver, and spleen of mice 18 days post-immunization [ 71 ]. These studies have shown that BCG vaccination is involved with increased ILCs, yet there is room for further study regarding the interplay between BCG vaccination and its effects on ILCs post-infection with M. tb .…”
Section: Effects Of Bcg Vaccine On Natural Killer Cells and Innate Ly...supporting
confidence: 67%
See 1 more Smart Citation
“…Steigler et al showed that intranasal vaccination of mice resulted in increased levels of ILC1, ILC2, and ILC3 within lungs, 4 weeks post-immunization [ 41 ]. This is supported in future studies by Gunasena et al, showing increased levels of ILC1 and ILC3 in the tissue samples from lungs, liver, and spleen of mice 18 days post-immunization [ 71 ]. These studies have shown that BCG vaccination is involved with increased ILCs, yet there is room for further study regarding the interplay between BCG vaccination and its effects on ILCs post-infection with M. tb .…”
Section: Effects Of Bcg Vaccine On Natural Killer Cells and Innate Ly...supporting
confidence: 67%
“…Although Corral et al found that BCG vaccination showed no advantageous post-infection increase in the levels of other ILCs apart from ILC1, other studies have found there to be an increase in ILCs in response to the BCG vaccination itself [ 33 , 70 , 71 ]. Steigler et al showed that intranasal vaccination of mice resulted in increased levels of ILC1, ILC2, and ILC3 within lungs, 4 weeks post-immunization [ 41 ].…”
Section: Effects Of Bcg Vaccine On Natural Killer Cells and Innate Ly...mentioning
confidence: 99%
“…Mtb possesses distinct mechanisms to evade our immune system, manifesting in various strategies, such as redirecting host immune responses towards tolerance and exhaustion, a characteristic also observed in other mycobacterial species, including BCG [41, 42]. Of note, BCG-elicited T cells were shown more likely to have an exhausted phenotype as compared to those elicited by BCGΔBCG1419c [43].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue processing for flow cytometry staining: Tissue processing and flow cytometry staining were performed as previously described 46 . Briefly, mice were euthanized, and their lungs, spleens, and blood were processed.…”
Section: Confirmation and Sample Collectionmentioning
confidence: 99%